Knowledge, attitude and practices regarding food labeling among Medical & Nursing students in a medical college in Madhya Pradesh, India: A cross-sectional study - Dwivedi Shatkratu; Gupta Amarnath; Das Abhijit; Dubey Shubhra; Kumar Rohit Bhupendra; Dwivedi Sudeept (Global Journal of Medicine and Public Health, 2024)
Background Considering college students' food consumption habits and the importance of consumers' comprehension and awareness of food labels in healthy food choices, our study primarily aims to assess the knowledge, attitude and practices (KAP) about food labelling among medical & nursing students and also to compare the KAP between them.